Relationships Between Air‐Sea CO2 Flux and New Production in the Equatorial Pacific. Issue 4 (30th March 2022) - Pittman, Nicholas A.; Strutton, Peter G.; Johnson, Robert; Matear, Richard J.; Sutton, Adrienne J.
Abstract: The equatorial Pacific is the largest oceanic source of carbon dioxide to the atmosphere. This outgassing varies depending on the El Niño‐Southern Oscillation (ENSO) and decadal climate variability. New production, the amount of phytoplankton net primary production driven by upwelled nitrate, plays a significant role in modulating air‐sea CO2 fluxes as the biological carbon pump removes carbon from the surface ocean. We aim to understand how the physical drivers of sea surface temperature and wind speed influence interannual and decadal variability of the equatorial Pacific carbon cycle. In the equatorial Pacific, there are three biogeochemical regimes: the upwelling cold tongue east of 140°W and south of the equator (3°N–15°S); the eastern Pacific warm pool north of the equator (3°–15°N); and the 28.5°C western Pacific warm pool, west of 140°W. We find that between 2000 and 2020, air‐sea CO2 flux and Δ p CO2 increased in the cold tongue (45 mmolC m −2  yr −2, 1.5 μatm yr −1, respectively) but decreased elsewhere, while new production decreased everywhere. The western Pacific occasionally became a weak carbon sink, depending on ENSO and this sink was strongest at 165°E during central Pacific "Modoki" El Niño events. We find that changes in wind speed, temperature and ENSO frequency have altered the surface carbon budget. The mean basin‐wide (150°E−90°W and 15°N–15°S) new production for 2000–2020 was 1.2 ± 0.1 PgC yr −1 and air‐sea CO2 flux was 0.5 ± 0.1 PgC yr −1 . New production decreased at −7.7 ± 1.6 TgC yr −2, compared to the CO2 flux trend of −1.7 ± 1.4 TgC yr −2 . Plain Language Summary: The equatorial Pacific is the largest source of carbon dioxide that outgasses from the ocean into the atmosphere. This outgassing varies depending on the El Niño‐Southern Oscillation (ENSO) and decadal changes in the climate. Winds in the eastern Pacific drive upwelling which supplies nutrients and carbon to the surface. Some of this carbon is outgassed to the atmosphere, some is consumed by phytoplankton and can either move through the food web or sink into the ocean interior. We are interested in how much carbon is removed from the surface equatorial Pacific through outgassing of carbon and biological consumption. We find that changes in wind speeds, surface temperatures, freshening surface water and changing patterns of ENSO have influenced the equatorial Pacific carbon budget. For example, between 2000 and 2020, CO2 release to the atmosphere increased in the upwelling zone but decreased elsewhere, while biological consumption decreased everywhere. The western Pacific occasionally absorbs carbon from the atmosphere during central Pacific "Modoki" El Niño events, a particular type of El Niño that is becoming more frequent. Key Points: Decadal shifts in upwelling have increased CO2 flux in the cold tongue but not biological production, which is likely nutrient limited Increasing frequency of central Pacific El Niño events may amplify decadal CO2 flux trends and drive sink conditions in the west Increasing surface temperatures contribute to stratification and decreasing new production despite increasing dissolved inorganic carbon